Innovation of Cash Waqf Optimization Model through EBA Syariah - Satifa, Siti Annisa; Marenza, Silvya Eka; Riyadi, Muhammad Ikhsan (Faculty of Islamic Business and Management, 2023)
Restrictions on community activities have weakened the Indonesian economy. The government must find a solution to improve economic conditions. This study aims to develop a model that enhances Islamic social financial institutions and maximizes cash waqf potential in Indonesia for sustainable finance. The model will boost the national Islamic capital market and be analyzed with SWOT and Delphi methods. Data was collected via questionnaires from 19 academics and practitioners in the waqf and infrastructure sectors. Delphi test results showed all respondents believed there was a link between SWOT indicators and the feasibility of the model. This model contributes to economic recovery, Islamic capital market growth, sustainable social funding, optimized waqf potential, strengthened waqf financial institutions, and improved infrastructure management in Indonesia.